Wet Photolithography From Hydrogen Abstraction of a Quasi‐Orthogonal Aggregation‐Induced Emitter - Chen Cao; Huan Chen; Jia‐Ming Jin; Ji‐Hua Tan; Hong‐Ji Tan; Jiu‐Dong Lin; Wen‐Cheng Chen; Yi Yuan; Ze‐Lin Zhu; Chun‐Sing Lee (Advanced Science)
Abstract A new aggregation‐induced emission (AIE) luminogen is obtained by dimerizing acridin‐9(10H)‐one (Ac), an aggregation‐caused quenching (ACQ) effect monomer via an N─N bond and forming 9H,9′H‐[10,10′‐biacridine]‐9,9′‐dione (DiAc) with D2d symmetry. The quenching of DiAc in solution is ascribed to the enhanced basicity promoting hydrogen bonding and then a hydrogen abstraction (HA) reaction and/or an unallowed transition in frontier orbitals with the same symmetry facilitating intersystem crossing. It is found that emissive Ac is one product of the non‐emissive DiAc solution in the HA reaction activated by UV irradiation. By exploiting the AIE properties and the HA reaction of DiAc, photolithographic patterning is demonstrated with a paper wetted with DiAc solution.